Digital public service delivery oriented toward the government as a digital platform - Nguyen Dinh Quy (Journal of State Management, 2025)
The digital government, or the digital transformation of government operations, is an inevitable and prevailing trend among nations worldwide. Delivering digital public services based on the government as a digital platform allows state agencies to design digital services proactively, consistently, seamlessly, and interoperably. This trend in digital public service delivery is not just a possibility, but a necessity, enabling governments to implement digital transformation strategies comprehensively and effectively, thereby better-serving citizens and businesses.